Preparation method of multilayer core-shell structure lead-carbon composite material, lead-acid battery electrode and lead-acid battery
A multi-layer core-shell lead-carbon composite material addresses the cycle life issue in lead-acid batteries by forming a stable, efficient electron migration network, preventing PbSO4 crystal formation and reducing production costs.
Patent Information
- Application Number
- CN202211560706.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-12-07
AI Technical Summary
Lead-acid batteries suffer from limited cycle life due to the formation of non-conductive PbSO4 crystals on electrode plates, leading to a decrease in active material content and capacity, with existing solutions like adding carbon nanotubes being expensive and ineffective.
A multi-layer core-shell structured lead-carbon composite material is prepared by dispersing a lead-containing agent, forming a mesoporous and macroporous shell structure through sequential reactions and sintering, which prevents PbSO4 crystal formation and enhances electron migration.
The composite material improves cycle stability and electron migration efficiency, reducing production costs by using cheaper materials and preventing active material detachment, thus enhancing the performance and longevity of lead-acid batteries.
Smart Images

Figure CN115763762B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lead-acid batteries, and in particular to a preparation method of a multi-layer core-shell structured lead-carbon composite material, a lead-acid battery electrode and a lead-acid battery. Background Art
[0002] At present, lead-acid batteries are the most widely used electrochemical storage technology. They have many advantages, such as abundant raw materials, low cost of battery preparation process, high battery voltage, wide applicable temperature, high energy efficiency, low self-discharge and good safety. In particular, the maturity of battery component recycling technology has greatly reduced the pollution of lead poisoning to the environment, and can achieve a 99% recycling rate of battery raw materials. Of course, lead-acid batteries still have shortcomings in battery energy density and battery cycle life, especially in the cycle life sector, there is still a lot of room for improvement.
[0003] The main reason for the limited life of lead-acid batteries is that during use, a large amount of irreversible and non-conductive PbSO will be sulfided on the electrode plates. 4 crystals, while a large amount of PbSO 4 The generation of crystals will lead to a decrease in the content of active materials in lead-acid batteries, resulting in a decrease in the capacity and cycle life of lead-acid batteries. Therefore, in order to avoid the decrease in the cycle life of lead-acid batteries, the traditional approach is to add nanomaterials such as carbon nanotubes and graphene to the active materials to inhibit the sulfurization effect of the electrode plates, thereby increasing the cycle life of lead-acid batteries.
[0004] For example, patent CN105932294A discloses a nanocarbon conductive slurry, preparation method and application for lead-acid batteries, and specifically discloses mixing a nanocarbon material with a sulfuric acid oxidation solution, then heating and refluxing, while maintaining the slurry in a slightly boiling state with ultrasound, and after a certain reaction time, a fully oxidized nanocarbon conductive slurry is obtained. Although the added nanocarbon conductive slurry can improve the cycle performance of the lead-acid battery, there is still a problem of poor cycle performance. In addition, the use of nanocarbon conductive slurry is expensive, which increases the production cost of the lead-acid battery. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lead-carbon composite material with a multi-layer core-shell structure, which can significantly improve the cycle life of a lead-acid battery, and a method for preparing the multi-layer core-shell structure lead-carbon composite material with low production cost, a lead-acid battery electrode and a lead-acid battery.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a multilayer core-shell structure lead-carbon composite material comprises the following steps:
[0008] Dispersing the lead-containing agent in pure water and homogenizing it to obtain a dispersed mixture;
[0009] Adjusting the dispersed mixture to be weakly alkaline to obtain a dispersion;
[0010] Adding phenol, aldehyde and cross-linking agent to the dispersion in sequence for mixing reaction to obtain a first reaction solution;
[0011] Filtering and drying the first reaction liquid to obtain a first powder;
[0012] The first powder is subjected to a first high temperature sintering to obtain a lead core-mesoporous carbon material;
[0013] The lead core-mesoporous carbon material, pore-forming agent, phenol, aldehyde and water are mixed and reacted to obtain a second reaction solution;
[0014] Evaporating and drying the second reaction liquid to obtain a second powder;
[0015] performing a second high-temperature sintering on the second powder to obtain the multi-layer core-shell structure lead-carbon composite material;
[0016] Among them, the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside.
[0017] In some other embodiments, the molar ratio of the lead-containing agent, the phenol, the aldehyde and the cross-linking agent is 1: (0.30-0.50): (0.36-0.70): (0.15-0.38).
[0018] In some other embodiments, the lead-containing agent is dispersed in pure water, and after homogenization, the particle size of the dispersed mixture obtained is 1 micron to 2 microns.
[0019] In some other embodiments, the mass concentration of the dispersed mixture is 3% to 5%.
[0020] In some other embodiments, the temperature of the first high temperature sintering is 500° C. to 700° C., and the time is 2 h to 3 h.
[0021] In some other embodiments, the second high temperature sintering is performed at a temperature of 600° C. to 900° C. and for a time of 3 h to 5 h.
[0022] In some other embodiments, after the step of subjecting the first powder to a first high-temperature sintering step and before the step of subjecting the lead core-mesoporous carbon material, the pore former, the phenol, the aldehyde and the water to a mixed reaction, the following steps are further included:
[0023] Using a strong alkaline solution to alkali-etch the lead core-mesoporous carbon material for 40 minutes to 90 minutes;
[0024] The lead core-mesoporous carbon material after alkali etching is filtered and dried.
[0025] In some other embodiments, the step of mixing the lead core-mesoporous carbon material, the pore-forming agent, the phenol, the aldehyde and the water for reaction comprises the following specific steps:
[0026] The lead core-mesoporous carbon material is dispersed in pure water, a pore-forming agent, phenol and aldehyde are added, and the mixture is stirred at 40° C. to 60° C. for 6 h to 10 h;
[0027] Among them, the mass ratio of the lead core-mesoporous carbon material to the pore-forming agent is 1:(0.50-0.67); the molar ratio of the pore-forming agent, the phenol and the aldehyde is 1:(0.50-0.80):(0.60-1.22).
[0028] An active material for a lead-acid battery electrode, comprising at least the multi-layer core-shell structure lead-carbon composite material prepared by the method for preparing a multi-layer core-shell structure lead-carbon composite material as described in any of the above embodiments.
[0029] A lead-acid battery comprises the lead-acid battery electrode described in any one of the above embodiments.
[0030] Compared with the prior art, the present invention has at least the following advantages:
[0031] The above-mentioned preparation method of the multi-layer core-shell structure lead-carbon composite material, since the structure of the multi-layer core-shell structure lead-carbon composite material from the inside to the outside is lead core-mesoporous shell-macroporous shell, when the multi-layer core-shell structure lead-carbon composite material is applied to the electrode of the lead-acid battery, the pore size of the mesoporous shell is small, and the positive and negative active materials can be prevented from detaching from the alloy grid of the positive and negative electrodes without hindering the redox reaction of the positive and negative active materials, thereby effectively inhibiting the sulfurization of the electrode plate to generate a large amount of PbSO 4Crystals, thereby improving the cycle stability of the positive and negative electrodes of the lead-acid battery, thereby improving the cycle performance of the lead-acid battery; at the same time, due to the large specific surface area of the macroporous shell and good adsorption, the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active materials and the alloy grid, effectively avoiding the phenomenon that the active materials are easy to fall off during use, thereby improving the stability of the lead-acid battery electrode. In addition, the special structure of the multi-layer core-shell structure lead-carbon composite material provides a large amount of micro-reaction space for the redox reaction of the positive and negative active materials, effectively improving the reaction activity of the positive and negative materials, and the multi-layer structure of the outer macroporous shell-inner mesoporous shell forms an efficient electron migration network, which significantly improves the electron migration efficiency and effectively shortens the charging time of the lead-acid battery. Further, since the multi-layer core-shell structure lead-carbon composite material uses phenol, aldehyde, cross-linking agent and pore-forming agent as raw materials, instead of using traditional expensive nanomaterials such as carbon nanotubes and graphene, the production cost of lead-acid batteries is greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 A flow chart of a method for preparing a multilayer core-shell structure lead-carbon composite material according to one embodiment of the present invention;
[0034] Figure 2 This is a SEM image of the multilayer core-shell structure lead-carbon composite material prepared in Example 1 of the present invention;
[0035] Figure 3 This is a SEM image of a multilayer core-shell structure lead-carbon composite material prepared in Comparative Example 8 of the present invention;
[0036] Figure 4 This is a high-rate electrical performance test diagram of the lead-acid battery of Example 1 of the present invention;
[0037] Figure 5 This is a test diagram of the cycle electrical performance of the lead-acid battery of Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0039] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to suppress the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0041] The present application provides a method for preparing a multi-layer core-shell structure lead-carbon composite material, comprising the following steps: dispersing a lead-containing agent in pure water and performing a homogenization treatment to obtain a dispersed mixture; adjusting the dispersed mixture to be weakly alkaline to obtain a dispersed liquid; sequentially adding phenol, aldehyde, and a cross-linking agent to the dispersed liquid for mixed reaction to obtain a first reaction liquid; filtering and drying the first reaction liquid to obtain a first powder; performing a first high-temperature sintering on the first powder to obtain a lead core-mesoporous carbon material; performing a mixed reaction on the lead core-mesoporous carbon material, a pore-forming agent, phenol, aldehyde, and water to obtain a second reaction liquid; evaporating and drying the second reaction liquid to obtain a second powder; performing a second high-temperature sintering on the second powder to obtain the multi-layer core-shell structure lead-carbon composite material; wherein the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside.
[0042] The above-mentioned method for preparing the multi-layer core-shell structure lead-carbon composite material, since the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside, when the multi-layer core-shell structure lead-carbon composite material is applied to the electrode of the lead-acid battery, the pore size of the mesoporous shell is small, and the positive and negative electrode active materials can be prevented from detaching from the alloy grid of the positive and negative electrodes without hindering the redox reaction of the positive and negative electrode active materials, thereby effectively inhibiting the sulfidation of the electrode plate to generate a large amount of PbSO 4Crystals, thereby improving the cycle stability of the positive and negative electrodes of the lead-acid battery, thereby improving the cycle performance of the lead-acid battery; at the same time, due to the large specific surface area of the macroporous shell and good adsorption, the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active materials and the alloy grid, effectively avoiding the phenomenon that the active materials are easy to fall off during use, thereby improving the stability of the lead-acid battery electrode. In addition, the special structure of the multi-layer core-shell structure lead-carbon composite material provides a large amount of micro-reaction space for the redox reaction of the positive and negative active materials, effectively improving the reaction activity of the positive and negative materials, and the multi-layer structure of the outer macroporous shell-inner mesoporous shell forms an efficient electron migration network, which significantly improves the electron migration efficiency and effectively shortens the charging time of the lead-acid battery. Further, since the multi-layer core-shell structure lead-carbon composite material uses phenol, aldehyde, cross-linking agent and pore-forming agent as raw materials, instead of using traditional expensive nanomaterials such as carbon nanotubes and graphene, the production cost of lead-acid batteries is greatly reduced.
[0043] See also Figure 1 In order to better understand the technical solution and beneficial effects of the present application, the present application is further described in detail below in conjunction with specific examples. A method for preparing a multilayer core-shell lead-carbon composite material in one embodiment includes some or all of the following steps:
[0044] S110, dispersing the lead-containing agent in pure water, and performing homogenization to obtain a dispersed mixture.
[0045] It can be understood that the lead-containing agent is dispersed in pure water and homogenized to obtain a dispersed mixture with a small particle size and good uniformity. Further, in some other embodiments, the lead-containing agent is dispersed in pure water and homogenized to obtain a dispersed mixture with a particle size of 1 micron to 2 microns, so that it can be more fully contacted and reacted with phenol, aldehyde, cross-linking agent and lead-containing agent later.
[0046] S120, adjusting the dispersed mixture to be weakly alkaline to obtain a dispersion, providing a suitable alkaline environment for subsequent reaction of phenol, aldehyde, cross-linking agent with the lead-containing agent, so as to ensure that phenol, aldehyde, and cross-linking agent can be coated on the surface of the lead-containing agent to form a mesoporous phenolic resin layer. Further, in one embodiment, ammonia water is used to adjust the dispersed mixture to be weakly alkaline. In this embodiment, the weakly alkaline condition is pH=7-8.
[0047] S130, adding phenol, aldehyde, and a cross-linking agent to the dispersion in sequence for mixed reaction to obtain a first reaction solution, so as to ensure that a mesoporous phenolic resin layer can be formed on the surface of the lead-containing agent.
[0048] In this embodiment, the conditions of the mixed reaction are high-speed stirring for 4h to 7h to ensure that phenol, aldehyde and cross-linking agent can fully react. It is worth mentioning that since the phenol, aldehyde and cross-linking agent are stirred for 4h to 7h by high-speed stirring, on the one hand, high-speed stirring helps phenol and aldehyde to be evenly and reliably coated on the surface of the lead-containing agent to obtain a mesoporous phenolic resin layer with good uniformity and density, thereby ensuring that a lead core-phenolic resin material with good structural stability is obtained, so as to provide a good skeleton for the macroporous phenolic resin layer later; on the other hand, it helps phenol, aldehyde and cross-linking agent to disperse in the dispersion liquid to quickly obtain the first reaction liquid, thereby improving the production efficiency of preparing multi-layer core-shell structure lead-carbon composite materials. Further, in a preferred embodiment, phenol is first added to the dispersion liquid, then aldehyde is added, and finally a cross-linking agent is added to ensure that the solid powdered phenol can be well dispersed in the dispersion liquid, so as to help the aldehyde and cross-linking agent added later to be evenly and reliably coated on the surface of the lead-containing agent to generate a mesoporous phenolic resin layer with good uniformity and density, so as to ensure that a lead core-phenolic resin material with good structural stability is obtained.
[0049] S140, filtering and drying the first reaction liquid to obtain a first powder.
[0050] It is understandable that the first reaction liquid is first filtered to remove excess liquid, and then dried to remove excess reaction liquid from the first powder. It is worth mentioning that since the filtration is less destructive to the structure, the present application can obtain a lead core-phenolic resin material with a good structural skeleton by filtering the first reaction liquid, which can provide a good skeleton support for the subsequent macroporous phenolic resin layer.
[0051] S150, performing a first high-temperature sintering on the first powder, so that the mesoporous phenolic resin layer can be carbonized to form a mesoporous shell under the first high-temperature sintering condition, so as to obtain a lead core-mesoporous carbon material.
[0052] S160, mixing and reacting the lead core-mesoporous carbon material, pore-forming agent, phenol, aldehyde and water to obtain a second reaction solution, so as to coat the surface of the mesoporous shell to form a macroporous phenolic resin layer.
[0053] Furthermore, in some other embodiments, the step of mixing the lead core-mesoporous carbon material, pore former, phenol, aldehyde and water includes the following specific steps: dispersing the lead core-mesoporous carbon material in pure water, adding pore former, phenol and aldehyde, and continuously stirring at 40°C to 60°C for 6h to 10h.
[0054] It can be understood that the lead core-mesoporous carbon material is first dispersed in pure water so that the lead core-mesoporous carbon material can form a well-dispersed system in pure water, and at the same time, the condition of continuous stirring at 40°C to 60°C for 6h to 10h is coordinated so that phenol, aldehyde and pore-forming agent can evenly and reliably form a macroporous phenolic resin layer with good uniformity, strong connectivity and density on the surface of the mesocarbon layer.
[0055] It should be noted that in order to make the macroporous phenolic resin layer evenly and reliably coated on the surface of the lead core-mesoporous carbon material, the temperature is controlled at 40℃~60℃ so that the surface of the mesoporous shell can be slightly softened, thereby improving the bonding force between the macroporous phenolic resin layer and the mesoporous shell, and then improving the firmness of the connection between the macroporous phenolic resin layer and the mesoporous shell. In addition, 40℃~60℃ can make the pore former in the initial heating stage, so as to ensure that the pore former can pre-form uniform and smaller pores in the phenolic resin layer, so as to ensure that more phenolic resin layers can be coated on the surface of the mesoporous shell, so as to ensure that the macroporous phenolic resin layer has good adhesion to the mesoporous shell when it is just formed, so that a macroporous phenolic resin layer with strong connectivity to the mesoporous shell and relatively uniform pore size can be generated subsequently, so as to ensure that a dense multi-layer core-shell structure lead-carbon composite material with good structural stability and relatively uniform pore size is obtained, so as to improve the multi-layer core-shell structure lead-carbon composite material. After multiple cycles, it can still maintain an efficient electron migration network, effectively shortening the charging time of the lead-acid battery. In particular, when the second reaction liquid is subsequently poured into an evaporating dish and evaporated to a viscous state, and then the viscous second reaction liquid is placed in a 60°C to 70°C oven for drying, the entire pore-forming process of the pore-forming agent is carried out in a slow step-by-step manner, so that a macroporous shell with strong connectivity, relatively uniform pore size, good structural skeleton and density can be formed on the surface of the mesoporous shell, that is, it helps the pore-forming agent to construct an outer macroporous shell with a uniform connection structure connected to the inner surface mesoporous shell, so that the inner and outer shell layers are compactly connected, ensuring that the structure of the multi-layer core-shell lead-carbon composite material is not destroyed during multiple cycles.
[0056] S170, evaporating and drying the second reaction liquid to remove excess reaction liquid to obtain a second powder.
[0057] It can be understood that since the second reaction liquid contains a pore-forming agent, in order to ensure that the pore-forming agent can construct a uniform connection structure connecting the mesopores on the inner surface and the macropores on the outer surface, the present application first evaporates the second reaction liquid, so that on the one hand, the pore-forming agent slowly enters the pre-pore-forming stage of pore-forming, and on the other hand, the macroporous phenolic resin layer can be reliably and evenly solidified on the surface of the mesoporous shell to obtain a macroporous phenolic resin layer with good connection strength with the mesoporous shell. Further, in the present embodiment, the step of evaporating and drying the second reaction liquid comprises the following specific steps: pouring the second reaction liquid into an evaporating dish and evaporating it to a viscous state, and then drying the viscous second reaction liquid in a 60°C to 70°C oven, so that the macroporous phenolic resin layer can be reliably and evenly solidified on the surface of the mesoporous shell, and the evaporation temperature is 60°C to 70°C, so that the pore-forming agent can enter the pre-pore-forming temperature rising stage, at which time the pore-forming agent slowly enters the pre-pore-forming stage of pore-forming, so as to ensure that the pore size of the macroporous phenolic resin layer increases slowly and evenly, and at the same time, the surface of the mesoporous shell can be further softened, so that the macroporous phenolic resin layer can be firmly attached. on the surface of the mesoporous shell, so that it not only ensures that the pore-forming agent can prepare a macroporous shell with relatively uniform pore size, but also ensures that the bonding force between the macroporous phenolic resin layer and the mesoporous shell is good, thereby improving the firmness of the connection between the macroporous phenolic resin layer and the mesoporous shell, so as to avoid the pore-forming agent directly entering the second high-temperature sintering, the pore-forming agent heating rate is too fast to obtain a macroporous shell with relatively uniform pore size, the pore-forming agent can construct an outer macroporous shell with a uniform connection structure connecting the inner surface mesoporous shell to ensure that the pore-forming agent can construct an outer macroporous shell with a uniform connection structure connecting the inner surface mesoporous shell, so that the inner and outer shells are compactly connected, ensuring that the structure of the multi-layer core-shell structure lead-carbon composite material is not destroyed during multiple cycles.
[0058] S180. Performing a second high-temperature sintering on the second powder so that the macroporous phenolic resin layer can be carbonized to form a macroporous shell, thereby preparing the multi-layer core-shell structure lead-carbon composite material; wherein the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside.
[0059] The above-mentioned method for preparing a multi-layer core-shell structure lead-carbon composite material, since the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside, that is, the structure of the multi-layer core-shell structure lead-carbon composite material is Pb@Cme / Cma, when the multi-layer core-shell structure lead-carbon composite material is applied to the electrode of a lead-acid battery, the pore size of the mesoporous shell is relatively small. Without hindering the oxidation-reduction reaction of the positive and negative active materials, the positive and negative active materials can be prevented from escaping from the alloy grid of the positive and negative electrodes, thereby effectively inhibiting the sulfurization of the electrode plates to generate a large amount of PbSO4 crystals, thereby improving the cycle stability of the positive and negative electrodes of the lead-acid battery, thereby improving the cycle performance of the lead-acid battery; at the same time, due to the large specific surface area of the macroporous shell and good adsorption, the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active materials and the alloy grid, effectively avoiding the phenomenon of easy shedding of the active materials during use, thereby improving the stability of the lead-acid battery electrode. In addition, the special structure of the multi-layer core-shell lead-carbon composite material provides a large amount of micro-reaction space for the redox reactions of the positive and negative active materials, effectively improving the reaction activity of the positive and negative electrode materials. The multi-layer structure of the outer macroporous shell-inner mesoporous shell forms an efficient electron migration network, which significantly improves the electron migration efficiency and effectively shortens the charging time of the lead-acid battery.
[0060] Furthermore, since the multilayer core-shell structure lead-carbon composite material uses phenol, aldehyde, cross-linking agent and pore-forming agent as raw materials, instead of using traditional expensive nanomaterials such as carbon nanotubes and graphene, the production cost of lead-acid batteries is greatly reduced.
[0061] In other embodiments, the above steps S130 to S170 can be repeated to obtain a combination of multiple layers of different structures on the surface of the lead-containing agent to increase the diversity of the multi-layer core-shell structure lead-carbon composite material, to increase the market competitiveness of the multi-layer core-shell structure lead-carbon composite material, and to broaden the application field of the multi-layer core-shell structure lead-carbon composite material.
[0062] In some other embodiments, the molar ratio of the lead-containing agent, the phenol, the aldehyde and the cross-linking agent is 1: (0.30-0.50): (0.36-0.70): (0.15-0.38). It can be understood that if the molar ratio of the lead-containing agent, phenol, aldehyde and cross-linking agent is lower than 1: 0.30: 0.36: 0.15, the coating layer of the phenolic resin formed on the surface of the lead-containing agent is relatively loose, resulting in a larger and incomplete pore size of the mesoporous shell, which makes the mesoporous shell easy to fall off during use. If the molar ratio of the lead-containing agent, phenol, aldehyde and cross-linking agent is higher than 1: 0.50: 0.70: 0.38, it is easy to cause the adhesion and uniformity of the phenolic resin formed on the surface of the lead-containing agent to be poor, thereby affecting the firmness of the combination of the mesoporous shell and the lead-containing agent. Therefore, the applicant has found through research that when the molar ratio of the lead-containing agent, the phenol, the aldehyde and the cross-linking agent is 1: (0.30-0.50): (0.36-0.70): (0.15-0.38), a mesoporous phenolic resin layer can be formed on the surface of the lead-containing agent. Especially when used in combination with the dispersed mixture having a mass concentration of 3% to 5%, a lead core-mesoporous carbon material with good uniformity and stable structure can be formed on the surface of the lead-containing agent, so that the lead core-mesoporous carbon material can provide a good supporting skeleton for the subsequent macroporous phenolic resin layer, thereby ensuring that the macroporous phenolic resin layer can be reliably and evenly coated on the surface of the mesoporous shell to obtain a macroporous shell with good uniformity and stable structural skeleton, thereby ensuring that the multi-layer core-shell structure lead-carbon composite material still maintains a good structural skeleton after multiple cycles of use, and ensuring that the multi-layer core-shell structure lead-carbon composite material can still maintain an efficient electron migration network after multiple cycles of use, thereby improving the cycle performance of the positive and negative electrodes of the lead-acid battery, and ensuring that the lead-acid battery still has good electron migration efficiency under long-term use, effectively shortening the charging time of the lead-acid battery.
[0063] In some other embodiments, the temperature of the first high temperature sintering is 500℃~700℃, and the time is 2h~3h, so as to ensure that the mesoporous phenolic resin layer can be fully carbonized into a mesoporous shell. Further, in some other embodiments, the pore size of the mesopore is 2nm~50nm. Further, in the step of subjecting the first powder to the first high temperature sintering, the following specific steps are included: the dried first powder is placed in a tubular furnace filled with an inert atmosphere and sintered at 500℃~700℃ for 2h~3h, for example, the inert atmosphere is nitrogen.
[0064] In some other embodiments, the lead core-mesoporous carbon material is dispersed in pure water to obtain a lead core-mesoporous carbon material mixed solution, and the mass concentration of the lead core-mesoporous carbon material mixed solution is 3% to 5%, so as to ensure that the pore-forming agent, phenol and aldehyde added subsequently can form a macroporous phenolic resin layer with good uniformity on the surface of the 3% to 5% lead core-mesoporous carbon material. It is worth mentioning that the present application sets the mass concentration of the lead core-mesoporous carbon material mixed solution to be the same as the mass concentration of the dispersed mixture to ensure good bonding between the mesoporous shell and the macroporous phenolic resin layer, thereby improving the firmness of the bonding between the two.
[0065] Furthermore, in order to ensure that the pore former, phenol and aldehyde can form a strongly connected and dense macroporous phenolic resin layer on the surface of the lead core-mesoporous carbon material, in some other embodiments, the mass ratio of the lead core-mesoporous carbon material to the pore former is 1:(0.5~0.67); the molar ratio of the pore former, the phenol and the aldehyde is 1:(0.5~0.8):(0.6~1.22).
[0066] It can be understood that if the molar ratio of the pore-forming agent, lead core-mesoporous carbon material, phenol and aldehyde is lower than 1:0.5:0.6, the macroporous phenolic resin layer will be loose and the firmness of the combination of the macroporous phenolic resin layer and the mesoporous shell will be affected. If the molar ratio of the pore-forming agent, lead core-mesoporous carbon material, phenol and aldehyde is higher than 1:0.8:1.22, it will not only cause waste of raw materials, but also reduce the adhesion between the macroporous phenolic resin layer and the mesoporous shell, thereby reducing the firmness of the combination of the macroporous phenolic resin layer and the mesoporous shell. Therefore, the applicant has found through research that when the molar ratio of the pore-forming agent, the lead core-mesoporous carbon material, the phenol and the aldehyde is controlled at 1:(0.5-0.8):(0.6-1.22), and the mass ratio of the lead core-mesoporous carbon material to the pore-forming agent is 1:(0.5-0.67), a macroporous phenolic resin layer with good bonding, uniform pore size and good density can be generated on the surface of the mesoporous shell, thereby ensuring the firmness of the connection between the mesoporous shell and the macroporous phenolic resin layer.
[0067] In some other embodiments, when the lead core-mesoporous carbon material is dispersed in pure water and a pore former, phenol and aldehyde are added, the pore former is added in a multiple step-by-step incremental manner, which can construct a uniform connection structure connecting the mesopores on the inner surface and the macropores on the outer surface, so that the inner and outer shell layers are compactly connected, ensuring that the structure of the multi-layer core-shell structure lead-carbon composite material is not destroyed during multiple cycles.
[0068] It should be noted that if the pore-forming agent is added in a one-time manner, the pore size of the macroporous phenolic resin layer will be greatly different, resulting in different pore sizes of the macroporous shell, which will cause the electron migration efficiency of the lead-acid battery to be relatively poor under long-term use, which not only reduces the number of cycles of the lead-acid battery, but also prolongs the charging time of the lead-acid battery; if the pore-forming agent is added in a multi-step decreasing amount or equal amount or variable amount, not only will the pore size of the macroporous shell be greatly different, but also the structural stability of the multi-layer core-shell structure lead-carbon composite material will be affected. The applicant has found that by setting the pore-forming agent to be added in multiple step-by-step increments, the pore size of the macroporous shell will be greatly different, and the structural stability of the multi-layer core-shell structure lead-carbon composite material will be affected. The method makes it possible to generate the pore size of the macroporous phenolic resin layer in a slowly progressive manner, thereby ensuring that the macroporous phenolic resin layer can be uniformly and reliably coated on the surface of the mesoporous shell to obtain a macroporous shell with uniform pore size, good connectivity and relative density, thereby ensuring that a multilayer core-shell structured lead-carbon composite material with stable structure and uniform pore size is obtained, thereby ensuring that the multilayer core-shell structured lead-carbon composite material can still maintain an efficient electron migration network after multiple cycles of use, thereby ensuring that the lead-acid battery still has good electron migration efficiency under long-term use, thus improving the cycle performance of the positive and negative electrodes of the lead-acid battery, and effectively shortening the charging time of the lead-acid battery.
[0069] Furthermore, in a preferred embodiment, the multiple step-by-step incremental addition method is: the first addition amount is 1 / 16 of the total amount of the pore-forming agent, the second addition amount is 1 / 8 of the total amount of the pore-forming agent, the third addition amount is 3 / 16 of the total amount of the pore-forming agent, the fourth addition amount is 1 / 4 of the total amount of the pore-forming agent, and finally 3 / 8 of the pore-forming agent is added, and the pore-forming agent needs to be stirred for 20 minutes to 30 minutes each time it is added.
[0070] It can be understood that since the amount added for the first time is 1 / 16 of the total amount of the pore-forming agent, which is relatively small compared to the amount added in the following four times, a small amount of pore-forming agent can pre-form a uniform and smaller pore size in the phenolic resin layer, so as to ensure that the macroporous phenolic resin layer can have good adhesion with the mesoporous shell when it is just formed, so as to improve the bonding force between the macroporous phenolic resin layer and the mesoporous shell, effectively avoid the phenomenon that the active material is easy to fall off during use, thereby improving the stability of the lead-acid battery electrode, so that a macroporous phenolic resin layer with strong connectivity to the mesoporous shell and relatively uniform pore size can be generated later, so as to ensure that a dense multilayer core-shell structure lead-carbon composite material with good structural stability and relatively uniform pore size is obtained, so as to improve the multilayer core-shell structure lead-carbon composite material. After multiple cycles of use, it can still maintain an efficient electron migration network, significantly improve the electron migration efficiency, effectively shorten the charging time of the lead-acid battery, and at the same time ensure that the specific surface area of the macroporous shell prepared later is large and has good adsorption, so that the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active material and the alloy grid.
[0071] In some other embodiments, the temperature of the second high temperature sintering is 600℃~900℃, and the time is 3h~5h, to ensure that the macroporous phenolic resin layer can be fully carbonized into a macroporous shell. Further, in some other embodiments, the pore size of the macropores is greater than 50nm; in a preferred embodiment, the pore size of the macropores is 50nm~100nm. Further, in the step of subjecting the second powder to the second high temperature sintering, the following specific steps are included: the dried second powder is placed in a tubular furnace filled with an inert atmosphere and sintered at 600℃~900℃ for 3h~5h, for example, the inert atmosphere is nitrogen, to ensure that the macroporous phenolic resin layer can be fully carbonized into a macroporous shell.
[0072] In some other embodiments, the temperature of the second high-temperature sintering is higher than the temperature of the first high-temperature sintering, and the time of the second high-temperature sintering is longer than the time of the first high-temperature sintering. In this way, it can be ensured that the macroporous phenolic resin layer has a larger pore size, so that the specific surface area of the macroporous shell is larger and has good adsorption properties, so that the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active materials and the alloy grid, effectively avoiding the phenomenon of easy falling off of the active materials during use, and thereby improving the stability of the lead-acid battery electrodes.
[0073] In some other embodiments, after the step of subjecting the first powder to a first high-temperature sintering step and before the step of mixing and reacting the lead core-mesoporous carbon material, pore-forming agent, phenol, aldehyde and water, the following steps are also included: subjecting the lead core-mesoporous carbon material to alkaline etching with a strong alkaline solution; and filtering and drying the lead core-mesoporous carbon material that has been alkaline etched.
[0074] It can be understood that the present application uses a strong alkaline solution to alkali-etch the lead core-mesoporous carbon material, so that an uneven structure can be formed on the surface of the mesoporous shell, thereby improving the roughness of the mesoporous shell. In this way, the uneven structure can provide a better attachment point for the macroporous phenolic resin layer, so that the macroporous phenolic resin layer can be well embedded and attached to the uneven structure of the mesoporous shell, thereby improving the connection strength between the mesoporous shell and the macroporous phenolic resin layer, and then the alkali-etched lead core-mesoporous carbon material is filtered and dried to remove excess strong alkaline solution to prevent excess strong alkaline solution from entering the next link to affect the structure of the macroporous shell and cause deformation.
[0075] Further, in one of the embodiments, the strong alkaline solution comprises at least one of a NaOH solution and a KOH solution. Further, in one of the embodiments, the mass concentration of the strong alkaline solution is 4% to 5%.
[0076] In some other embodiments, the lead-containing agent includes at least one of lead powder and lead dioxide powder.
[0077] In some other embodiments, the phenol includes at least one of resorcinol and meta-cresol. It is understandable that since the chemical structures of resorcinol and meta-cresol are both centrosymmetric structures, the formed mesoporous shell and macroporous shell have good symmetry, so as to ensure that the mesoporous shell and macroporous shell with good uniformity and compactness are obtained. Further, in a preferred embodiment, the phenol is resorcinol, and since there are two symmetrical OH groups on the benzene ring of resorcinol, a uniform and compact mesoporous shell and macroporous shell can be formed on the surface of the lead-containing agent.
[0078] In some other embodiments, the aldehyde includes at least one of formaldehyde, acetaldehyde and propionaldehyde. It can be understood that since formaldehyde, acetaldehyde and propionaldehyde are all short-chain linear small molecule structures, the short-chain linear small molecule structure can form a uniform and dense network of mesoporous shells and macroporous shells with symmetrical benzene ring-containing resorcinol or meta-cresol to ensure that the surface of the lead-containing agent is coated to form a network of mesoporous shells and macroporous shells with good connectivity. Further, in a preferred embodiment, the aldehyde is formaldehyde.
[0079] Furthermore, in one of the embodiments, since the types of aldehydes and phenols used in the mesoporous shell are the same as those used in the macroporous shell, the compatibility between the mesoporous shell and the macroporous phenolic resin layer is better, so that the macroporous phenolic resin layer can be better attached to the surface of the mesoporous shell, thereby improving the bonding force between the macroporous phenolic resin layer and the mesoporous shell, and further improving the firmness of the connection between the macroporous shell and the mesoporous shell.
[0080] In some other embodiments, the pore-forming agent includes at least one of silicon dioxide and sodium chloride. The particle size of the pore-forming agent is 50 nm to 80 nm.
[0081] In some other embodiments, the crosslinking agent is tetraethyl orthosilicate.
[0082] In some other embodiments, after the step of performing a second high-temperature sintering on the second powder to obtain the multi-layer core-shell structure lead-carbon composite material, the following step is also included: dispersing the multi-layer core-shell structure lead-carbon composite material in pure water, and performing ultrasonic dispersion, filtration, and drying to obtain a high-purity multi-layer core-shell structure lead-carbon composite material, so as to ensure that a high-purity multi-layer core-shell structure lead-carbon composite material can be provided for the active material of the lead-acid battery electrode in the future, so as to prepare a lead-acid battery with excellent performance.
[0083] The present application also provides an active material for a lead-acid battery electrode, at least comprising the multilayer core-shell structure lead-carbon composite material prepared by the multilayer core-shell structure lead-carbon composite material preparation method as described in any of the above embodiments. It can be understood that the multilayer core-shell structure lead-carbon composite material prepared in any of the above embodiments is applied to the active material of the lead-acid battery electrode. Since the structure of the multilayer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside, the macroporous shell of the multilayer core-shell structure lead-carbon composite material has good adsorption, so that the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active material and the alloy grid, effectively avoiding the phenomenon that the active material is easy to fall off during use, thereby improving the stability of the lead-acid battery electrode. At the same time, the pore size of the mesoporous shell is small, and the positive and negative active materials can be prevented from detaching from the alloy grid of the positive and negative electrodes without hindering the redox reaction of the positive and negative active materials, thereby effectively inhibiting the sulfurization of the electrode plate to generate a large amount of PbSO 4 Crystals, thereby improving the cycle stability of the positive and negative electrodes of the lead-acid battery, thereby improving the cycle performance of the lead-acid battery. At the same time, the special structure of the multi-layer core-shell lead-carbon composite material provides a large amount of micro-reaction space for the redox reaction of the positive and negative active materials, effectively improving the reaction activity of the positive and negative electrode materials. The multi-layer structure of the outer macroporous shell-inner mesoporous shell forms an efficient electron migration network, which significantly improves the electron migration efficiency and effectively shortens the charging time of the lead-acid battery.
[0084] Furthermore, in some other embodiments, the application of the multi-layer core-shell structure lead-carbon composite material in the active material of the lead-acid battery electrode includes the following specific steps: mixing the multi-layer core-shell structure lead-carbon composite material with lead sulfate, dilute sulfuric acid, and pure water to form a slurry, then applying the slurry on the alloy grid, and finally drying it to obtain a lead-acid battery electrode, the electrode including a positive electrode and a negative electrode.
[0085] The present application also provides a lead-acid battery, including the lead-acid battery electrode described in any of the above embodiments. The above-mentioned lead-acid battery, specifically, is obtained by assembling, acid-filling, and chemically forming the dried lead-acid battery electrodes. Since the active materials of the lead-acid battery electrodes are all made of multi-layer core-shell structured lead-carbon composite materials, a large amount of micro-reaction space is provided for the redox reaction of the positive and negative active materials, which effectively improves the reaction activity of the positive and negative electrode materials, and the multi-layer structure of the outer macroporous shell-inner mesoporous shell forms an efficient electron migration network, which significantly improves the electron migration efficiency, effectively shortens the charging time of the lead-acid battery, and improves the cycle performance of the lead-acid battery. For details, please refer to Figures 4 to 5 It can be seen from the electrical performance diagram that when the multi-layer core-shell structure lead-carbon composite material of the present application is applied to a lead-acid battery, after multiple cycles, the high-rate discharge capacity does not decrease, and the rate performance is good.
[0086] Compared with the prior art, the present invention has at least the following advantages:
[0087] The above-mentioned method for preparing the multi-layer core-shell structure lead-carbon composite material, since the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside, when the multi-layer core-shell structure lead-carbon composite material is applied to the electrode of the lead-acid battery, the pore size of the mesoporous shell is small, and the positive and negative electrode active materials can be prevented from being separated from the alloy grid of the positive and negative electrodes without hindering the redox reaction of the positive and negative electrode active materials, thereby effectively inhibiting the sulfurization of the electrode plate to generate a large amount of PbSO 4 Crystals, thereby improving the cycle stability of the positive and negative electrodes of the lead-acid battery, thereby improving the cycle performance of the lead-acid battery; at the same time, due to the large specific surface area of the macroporous shell and good adsorption, the positive and negative active materials can be more firmly adhered to the alloy grid of the positive and negative electrodes, thereby improving the connection strength between the active materials and the alloy grid, effectively avoiding the phenomenon that the active materials are easy to fall off during use, thereby improving the stability of the lead-acid battery electrode. In addition, the special structure of the multi-layer core-shell structure lead-carbon composite material provides a large amount of micro-reaction space for the redox reaction of the positive and negative active materials, effectively improving the reaction activity of the positive and negative materials, and the multi-layer structure of the outer macroporous shell-inner mesoporous shell forms an efficient electron migration network, which significantly improves the electron migration efficiency and shortens the battery charging time. Further, since the multi-layer core-shell structure lead-carbon composite material uses phenol, aldehyde, cross-linking agent and pore-forming agent as raw materials, instead of using traditional expensive nanomaterials such as carbon nanotubes and graphene, the production cost of lead-acid batteries is greatly reduced.
[0088] Some specific examples are given below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0089] Example 1
[0090] Dispersing 20 kg of lead powder in 500 kg of pure water and homogenizing the mixture to obtain a dispersed mixture with a mass concentration of 4%, wherein the particle size of the dispersed mixture obtained after the homogenization is 2 microns; adjusting the pH of the dispersed mixture to 7.5 with ammonia water to obtain a dispersed liquid; adding 4.25 kg of resorcinol, 4.31 kg of 37% formaldehyde, and then adding 4.02 kg of tetraethyl orthosilicate to the dispersed liquid in sequence and stirring at high speed for 5 hours to obtain a first reaction liquid; filtering the first reaction liquid and drying it to obtain a first powder;
[0091] The lead core-mesoporous carbon material is alkali-etched for 60 minutes using a 4% NaOH solution; the lead core-mesoporous carbon material after alkali etching is filtered and dried, and the first powder after drying is placed in a tubular furnace filled with a nitrogen atmosphere for a first high-temperature sintering, wherein the temperature of the first high-temperature sintering is 600° C., and the sintering is performed for 2.5 hours to obtain the lead core-mesoporous carbon material;
[0092] Dispersing 12 kg of the lead core-mesoporous carbon material in 300 kg of pure water to obtain a lead core-mesoporous carbon material mixed solution with a mass concentration of 4%, adding 7.24 kg of sodium chloride solid with a particle size of 70 nm, 9.50 kg of resorcinol and 10.00 kg of 37% formaldehyde, wherein the sodium chloride solid is added in multiple step-by-step increments, the first addition amount is 1 / 16 of the total amount of the sodium chloride solid, the second addition amount is 1 / 8 of the total amount of the sodium chloride solid, the third addition amount is 3 / 16 of the total amount of the sodium chloride solid, the fourth addition amount is 1 / 4 of the total amount of the sodium chloride solid, and finally adding 3 / 8 of the sodium chloride solid, and stirring for 25 minutes after each addition of the sodium chloride solid, and stirring is continued at 50° C. for 7 hours to obtain a second reaction solution;
[0093] The second reaction liquid is poured into an evaporating dish and evaporated to a viscous state, and then placed in a 5°C oven for drying. The dried second powder is placed in a tubular furnace filled with a nitrogen atmosphere for a second high-temperature sintering, wherein the temperature of the second high-temperature sintering is 800°C for 4 hours to obtain a multilayer core-shell structure lead-carbon composite material; wherein the structure of the multilayer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from inside to outside;
[0094] The multi-layer core-shell structure lead-carbon composite material is dispersed in pure water, and ultrasonic dispersion, suction filtration and drying are performed to obtain a multi-layer core-shell structure lead-carbon composite material with high purity.
[0095] Example 2
[0096] 21 kg of lead dioxide powder is dispersed in 700 kg of pure water and homogenized to obtain a dispersed mixture with a mass concentration of 3%, wherein the particle size of the dispersed mixture obtained after the homogenization is 1 micron; the pH of the dispersed mixture is adjusted to 7 with ammonia water to obtain a dispersion liquid; 3.29 kg of m-cresol, 1.79 kg of 37% acetaldehyde, and 3.17 kg of tetraethyl orthosilicate are sequentially added to the dispersion liquid and stirred at high speed for 4 hours to obtain a first reaction liquid; the first reaction liquid is filtered and dried to obtain a first powder;
[0097] The lead core-mesoporous carbon material is alkali-etched for 40 minutes using a 4% KOH solution; the lead core-mesoporous carbon material after alkali etching is filtered and dried, and the first powder after drying is placed in a tubular furnace filled with a nitrogen atmosphere for a first high-temperature sintering, wherein the temperature of the first high-temperature sintering is 500° C., and the sintering is performed for 2 hours to obtain the lead core-mesoporous carbon material;
[0098] Dispersing 12 kg of the lead core-mesoporous carbon material in 400 kg of pure water to obtain a lead core-mesoporous carbon material mixed solution with a mass concentration of 3%, adding 6.00 kg of silicon dioxide with a particle size of 50 nm, 5.94 kg of meta-cresol and 2.65 kg of 37% acetaldehyde, wherein the silicon dioxide is added in multiple step-by-step increments, the first addition amount is 1 / 16 of the total amount of silicon dioxide, the second addition amount is 1 / 8 of the total amount of silicon dioxide, the third addition amount is 3 / 16 of the total amount of silicon dioxide, the fourth addition amount is 1 / 4 of the total amount of silicon dioxide, and finally adding 3 / 8 of the silicon dioxide, and stirring for 20 minutes after each addition of the silicon dioxide, and stirring is continued at 40° C. for 6 hours to obtain a second reaction solution;
[0099] The second reaction liquid is poured into an evaporating dish and evaporated to a viscous state, and then placed in a 60° C. oven for drying. The dried second powder is placed in a tubular furnace filled with a nitrogen atmosphere for a second high-temperature sintering, wherein the second high-temperature sintering temperature is 600° C. and the time is 3 hours, to obtain a multilayer core-shell structure lead-carbon composite material; wherein the structure of the multilayer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from inside to outside;
[0100] The multi-layer core-shell structure lead-carbon composite material is dispersed in pure water, and ultrasonic dispersion, suction filtration and drying are performed to obtain a multi-layer core-shell structure lead-carbon composite material with high purity.
[0101] Example 3
[0102] Dispersing 20 kg of lead powder in 400 kg of pure water and homogenizing the mixture to obtain a dispersed mixture with a mass concentration of 5%, wherein the particle size of the dispersed mixture obtained after the homogenization is 2 microns; adjusting the pH of the dispersed mixture to 8 with ammonia water to obtain a dispersed liquid; adding 5.31 kg of resorcinol, 5.48 kg of 37% formaldehyde, and then adding 7.64 kg of tetraethyl orthosilicate to the dispersed liquid in sequence and stirring at high speed for 7 hours to obtain a first reaction liquid; filtering the first reaction liquid and drying it to obtain a first powder;
[0103] The lead core-mesoporous carbon material is alkali-etched for 90 minutes using a 5% NaOH solution; the lead core-mesoporous carbon material after alkali etching is filtered and dried, and the first powder after drying is placed in a tubular furnace filled with a nitrogen atmosphere for a first high-temperature sintering, wherein the temperature of the first high-temperature sintering is 700° C., and the sintering is performed for 3 hours to obtain the lead core-mesoporous carbon material;
[0104] Dispersing 15 kg of the lead core-mesoporous carbon material in 300 kg of pure water to obtain a lead core-mesoporous carbon material mixed solution with a mass concentration of 5%, adding 9.80 kg of sodium chloride solid with a particle size of 80 nm, 14.70 kg of resorcinol and 16.25 kg of 37% formaldehyde, wherein the sodium chloride solid is added in multiple step-by-step increments, the first addition amount is 1 / 16 of the total amount of the sodium chloride solid, the second addition amount is 1 / 8 of the total amount of the sodium chloride solid, the third addition amount is 3 / 16 of the total amount of the sodium chloride solid, the fourth addition amount is 1 / 4 of the total amount of the sodium chloride solid, and finally adding 3 / 8 of the sodium chloride solid, and stirring for 30 minutes after each addition of the sodium chloride solid, and stirring is continued at 60° C. for 10 hours to obtain a second reaction solution;
[0105] The second reaction liquid is poured into an evaporating dish and evaporated to a viscous state, and then placed in a 70° C. oven for drying. The dried second powder is placed in a tubular furnace filled with a nitrogen atmosphere for a second high-temperature sintering, wherein the second high-temperature sintering temperature is 900° C. and the time is 5 hours, to obtain a multilayer core-shell structure lead-carbon composite material; wherein the structure of the multilayer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from inside to outside;
[0106] The multi-layer core-shell structure lead-carbon composite material is dispersed in pure water, and ultrasonic dispersion, suction filtration and drying are performed to obtain a multi-layer core-shell structure lead-carbon composite material with high purity.
[0107] Comparative Example 1
[0108] The difference from Example 1 is that the amounts of lead powder, resorcinol, formaldehyde and tetraethyl orthosilicate used in the preparation of the first reaction solution in Comparative Example 1 are different, and the amounts of sodium chloride solid, lead core-mesoporous carbon material resorcinol and 37% formaldehyde used in the preparation of the second reaction solution are different, that is, in Comparative Example 1, 20 kg of lead powder is dispersed in 689.66 kg of pure water, and homogenized to obtain a dispersed mixture with a mass concentration of 2.9%, and ammonia water is used to adjust the pH of the dispersed mixture to 7.5 to obtain a dispersion, and 2.12 kg of resorcinol, 2.35 kg of 37% formaldehyde, and then 2.02 kg of tetraethyl orthosilicate are added to the dispersion in sequence, and high-speed stirring is performed for 5 hours to obtain a first reaction solution;
[0109] 12 kg of the lead core-mesoporous carbon material is dispersed in 413.79 kg of pure water to obtain a lead core-mesoporous carbon material mixed solution with a mass concentration of 2.9%, and 4.81 kg of sodium chloride solid with a particle size of 70 nm, 3.62 kg of resorcinol and 3.31 kg of 37% formaldehyde are added to obtain a second reaction solution, and the rest remains unchanged.
[0110] Comparative Example 2
[0111] The difference from Example 1 is that the amounts of lead powder, resorcinol, formaldehyde and tetraethyl orthosilicate used in the preparation of the first reaction solution in Comparative Example 2 are different, and the amounts of sodium chloride solid, lead core-mesoporous carbon material resorcinol and 37% formaldehyde used in the preparation of the second reaction solution are different, that is, in Comparative Example 2, 20 kg of lead powder is dispersed in 392.16 kg of pure water, and homogenized to obtain a dispersed mixture with a mass concentration of 5.1%, and ammonia water is used to adjust the pH of the dispersed mixture to 7.5 to obtain a dispersion, and 6.38 kg of resorcinol, 6.27 kg of 37% formaldehyde, and then 8.04 kg of tetraethyl orthosilicate are added to the dispersion in sequence, and the mixture is stirred at high speed for 5 hours to obtain a first reaction solution;
[0112] 12 kg of the lead core-mesoporous carbon material is dispersed in 235.29 kg of pure water to obtain a lead core-mesoporous carbon material mixed solution with a mass concentration of 5.1%, and 8.44 kg of sodium chloride solid, 14.24 kg of resorcinol and 15.16 kg of 37% formaldehyde are added to obtain a second reaction solution, and the rest remains unchanged.
[0113] Comparative Example 3
[0114] The difference from Example 1 is that in Comparative Example 3, solid sodium chloride is added into the 4% lead core-mesoporous carbon material mixed solution at one time.
[0115] Comparative Example 4
[0116] The difference from Example 1 is that in Comparative Example 4, sodium chloride solid is added into the 4% lead core-mesoporous carbon material mixed solution in five equal portions.
[0117] Comparative Example 5
[0118] The difference from Example 1 is that, in Comparative Example 5, sodium chloride solid is added to the 4% lead core-mesoporous carbon material mixed solution in five steps, that is, the first addition amount is 3 / 8 of the total amount of sodium chloride solid, the second addition amount is 1 / 4 of the total amount of sodium chloride solid, the third addition amount is 3 / 16 of the total amount of sodium chloride solid, the fourth addition amount is 1 / 8 of the total amount of sodium chloride solid, and finally 1 / 16 of the sodium chloride solid is added.
[0119] Comparative Example 6
[0120] The difference from Example 1 is that, in Comparative Example 6, sodium chloride solid is added to the 4% lead core-mesoporous carbon material mixed solution in five times in an irregular manner, that is, the first addition amount is 1 / 8 of the total amount of sodium chloride solid, the second addition amount is 1 / 6 of the total amount of sodium chloride solid, the third addition amount is 1 / 8 of the total amount of sodium chloride solid, the fourth addition amount is 1 / 8 of the total amount of sodium chloride solid, and finally 11 / 24 of the sodium chloride solid is added.
[0121] Comparative Example 7
[0122] The difference from Example 1 is that a single-layer mesoporous shell (Pb@C me ), that is, in Example 6, 20 kg of lead powder is dispersed in 500 kg of pure water and homogenized to obtain a dispersed mixture with a mass concentration of 4%, wherein the particle size of the dispersed mixture obtained after homogenization is 2 microns; ammonia water is used to adjust the pH of the dispersed mixture to 7.5 to obtain a dispersion; 4.26 kg of resorcinol, 4.31 kg of 37% formaldehyde, and then 4.02 kg of tetraethyl orthosilicate are added to the dispersion in sequence and stirred at high speed for 5 hours to obtain a first reaction liquid; the first reaction liquid is filtered and then dried to obtain a first powder; the dried first powder is placed in a tubular furnace filled with a nitrogen atmosphere for a first high-temperature sintering, wherein the temperature of the first high-temperature sintering is 600°C, and the sintering is performed for 2.5 hours to obtain a lead core-mesoporous carbon material; the lead core-mesoporous carbon material is dispersed in pure water, and ultrasonically dispersed, filtered, and dried to obtain a high-purity single-layer core-shell structure lead-carbon composite material.
[0123] Comparative Example 8
[0124] The difference from Example 1 is that a single-layer macroporous shell (Pb@C ma), that is, in comparative example 5, 20 kg of lead powder is dispersed in 500 kg of pure water and homogenized to obtain a dispersed mixture with a mass concentration of 4%, wherein the particle size of the dispersed mixture obtained after homogenization is 2 microns; the pH of the dispersed mixture is adjusted to 7.5 with ammonia water to obtain a dispersion liquid; 7.24 kg of sodium chloride solid, 9.50 kg of resorcinol and 10.00 kg of 37% formaldehyde are added to the dispersion liquid in sequence, wherein the sodium chloride solid is added in multiple step-by-step increments, the first addition amount is 1 / 16 of the total amount of the sodium chloride solid, the second addition amount is 1 / 8 of the total amount of the sodium chloride solid, and the third addition amount is 3 / 16 of the total amount of the sodium chloride solid. 16, the fourth addition amount is 1 / 4 of the total amount of the sodium chloride solid, and finally 3 / 8 of the sodium chloride solid is added, and after each addition of the sodium chloride solid, it is necessary to stir for 25 minutes, and continue to stir at 50°C for 7 hours to obtain a second reaction liquid; the second reaction liquid is poured into an evaporating dish and evaporated to a viscous state, and is placed in a 60°C oven for drying, and the dried second powder is placed in a tubular furnace filled with a nitrogen atmosphere for a second high-temperature sintering, wherein the temperature of the second high-temperature sintering is 800°C, and the time is 4 hours to obtain a lead core-macroporous carbon material; the lead core-macroporous carbon material is dispersed in pure water, and ultrasonic dispersion, suction filtration, and drying are performed to obtain a high-purity single-layer core-shell structure lead-carbon composite material
[0125] The lead-carbon composite materials prepared in the above Examples 1 to 3 and Comparative Examples 1 to 8 were respectively applied to the positive and negative electrodes of lead-acid batteries, and the lead-acid batteries were respectively subjected to battery capacity and 100% DOD cycle life tests, internal observations of the lead-acid batteries, and charging time records, to obtain the test results in the following Table 1:
[0126] Table 1
[0127]
[0128]
[0129] As can be seen from Table 1, the number of cycle life and charging time of Examples 1 to 3 are significantly better than those of Comparative Examples 1 to 8. At the same time, after multiple cycles of use, the multilayer core-shell lead-carbon composite materials of Examples 1 to 3 can still maintain a good structural skeleton, that is, after 500 cycles, the positive and negative electrodes are not muddy, which is significantly better than the positive and negative electrodes of Comparative Examples 1 to 8. After 400 cycles, the positive and negative electrodes are slightly muddy. In particular, the comprehensive indicators of Example 1 are the best.
[0130] From the comparison between Example 1 and Comparative Examples 7 to 8, it can be seen that the multilayer core-shell structure lead-carbon composite material (Pb@C me / C ma ) is significantly better than the single-layer (Pb@Cme ) and Comparative Example 8 (Pb@C ma ). For further information, see Figure 2 and Figure 3 , Figure 2 This is the SEM image of the multilayer core-shell structure lead-carbon composite material prepared in Example 1. Figure 3 The SEM image of the single-layer core-shell structure lead-carbon composite material prepared in Comparative Example 8 is as follows: Figure 2 and Figure 3 By comparison, it can be seen that Figure 2 The multi-layer core-shell structure lead-carbon composite material has many and uniform pores, which can promote the migration of electrons and effectively improve the redox reaction between the electrolyte and the positive and negative active materials, thereby increasing the charge and discharge rate and effectively shortening the charge and discharge time. Figure 3 The pore sizes of the single-layer core-shell structure lead-carbon composite material are different, small and irregular, resulting in relatively low electron mobility, which in turn causes the number of cycle life and full charge time of Example 8 to be worse than those of Example 1.
[0131] From the comparison between Example 1 and Comparative Examples 1 to 2, it can be seen that when the mass ratio of the lead core-mesoporous carbon material to the pore-forming agent in Example 1 is 1:(0.50-0.67); the molar ratio of the pore-forming agent, the phenol and the aldehyde is 1:(0.50-0.80):(0.60-1.22), and the molar ratio of the lead-containing agent, the phenol, the aldehyde and the cross-linking agent is 1:(0.30-0.50):(0.36-0.70):(0.15-0.38), the number of cycles and charging time of the prepared multi-layer core-shell structured lead-carbon composite material are significantly better than those of Comparative Examples 1 to 2.
[0132] From the comparison between Example 1 and Comparative Examples 3 to 6, it can be seen that when the pore-forming agent of Example 1 is added in multiple step-by-step increments, the number of cycles and charging time of the prepared multi-layer core-shell structure lead-carbon composite material are significantly better than those of Comparative Examples 3 to 6.
[0133] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as a restriction on the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a multilayer core-shell structure lead-carbon composite material, characterized in that: The steps include: Dispersing the lead-containing agent in pure water and homogenizing it to obtain a dispersed mixture; Adjusting the dispersed mixture to be weakly alkaline to obtain a dispersion; Adding phenol, aldehyde and cross-linking agent to the dispersion in sequence for mixed reaction to obtain a first reaction solution; wherein the molar ratio of the lead-containing agent, the phenol, the aldehyde and the cross-linking agent is 1: (0.30-0.50): (0.36-0.70): (0.15-0.38); filtering and drying the first reaction liquid to obtain a first powder; The first powder is subjected to a first high temperature sintering to obtain a lead core-mesoporous carbon material; Dispersing the lead core-mesoporous carbon material in pure water, adding a pore-forming agent, phenol and aldehyde, and continuously stirring at 40° C. to 60° C. for 6 h to 10 h to obtain a second reaction solution; Wherein, the mass ratio of the lead core-mesoporous carbon material to the pore-forming agent is 1:(0.50-0.67); the molar ratio of the pore-forming agent, the phenol, and the aldehyde is 1:(0.50-0.80):(0.60-1.22); Pour the second reaction liquid into an evaporating dish and evaporate it into a viscous state, then put the viscous second reaction liquid into an oven at 60°C to 70°C to dry it to obtain a second powder; performing a second high-temperature sintering on the second powder to obtain the multi-layer core-shell structure lead-carbon composite material; Among them, the structure of the multi-layer core-shell structure lead-carbon composite material is lead core-mesoporous shell-macroporous shell from the inside to the outside.
2. The method for preparing a multilayer core-shell structure lead-carbon composite material according to claim 1, characterized in that: The lead-containing agent is dispersed in pure water, and after homogenization, the particle size of the dispersed mixture is obtained to be 1 micron to 2 microns.
3. The method for preparing a multilayer core-shell lead-carbon composite material according to claim 1, characterized in that: The mass concentration of the dispersed mixture is 3% to 5%.
4. The method for preparing a multilayer core-shell structure lead-carbon composite material according to claim 1, characterized in that: The temperature of the first high-temperature sintering is 500° C. to 700° C., and the time is 2 h to 3 h.
5. The method for preparing a multilayer core-shell structure lead-carbon composite material according to claim 1, characterized in that: The second high temperature sintering is performed at a temperature of 600° C. to 900° C. and for a time of 3 h to 5 h.
6. The method for preparing a multilayer core-shell structure lead-carbon composite material according to claim 1, characterized in that: After the step of subjecting the first powder to a first high-temperature sintering step and before the step of subjecting the lead core-mesoporous carbon material, the pore-forming agent, the phenol, the aldehyde and the water to a mixed reaction, the following steps are also included: Using a strong alkaline solution to alkali-etch the lead core-mesoporous carbon material for 40 minutes to 90 minutes; The lead core-mesoporous carbon material after alkali etching is filtered and dried.
7. An active material for a lead-acid battery electrode, characterized in that: At least includes the multi-layer core-shell structure lead-carbon composite material prepared by the multi-layer core-shell structure lead-carbon composite material preparation method as described in any one of claims 1 to 6.
8. A lead-acid battery, characterized in that: Comprising the lead-acid battery electrode as described in claim 7.
